1987
DOI: 10.1093/nar/15.3.1081
|View full text |Cite
|
Sign up to set email alerts
|

Chicken erythrocyte polynucleosomes which are soluble at physiological ionic strength and contain linker histones are highly enriched hi β-globin gene sequences

Abstract: Mature chicken erythrocyte polynucleosomes which are soluble at physiological ionic strength are enriched in beta-globin DNA sequences. Vitellogenin chromatin, which is not expressed in this tissue, is found in aggregation prone, salt insoluble chromatin. There is a direct correlation between the size of soluble fragments and the degree of globin gene enrichment, with the largest fragments being most highly enriched. The highly globin enriched (about 50 fold) polynucleosomes contain significantly elevated leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 27 publications
5
74
0
Order By: Relevance
“…Nucleosome Preparation and Histone Isolation-Chicken immature erythrocyte salt-soluble chromatin S150 was prepared as described previously (20). The salt-soluble chromatin fragments are enriched in acetylated core histones and will remain soluble in the kinase buffer, which contains 10 mM MgCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Nucleosome Preparation and Histone Isolation-Chicken immature erythrocyte salt-soluble chromatin S150 was prepared as described previously (20). The salt-soluble chromatin fragments are enriched in acetylated core histones and will remain soluble in the kinase buffer, which contains 10 mM MgCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The mono-, di-, tri-, and tetra-acetylated isoforms of H4 are marked as 1, 2, 3, and 4, respectively. Note that the content of H1 and H5 in fraction S150 is typically lower than that of the other chromatin fractions (65). (4); the net result is a low steady state level of highly acetylated histone isoforms in untreated immature cells.…”
Section: State Of Acetylation Of Dynamically Acetylated Histones Inmentioning
confidence: 97%
“…It has been suggested that acetylation of H4 during nucleosome assembly regulates the binding of H1 and the ability of chromatin to condense (34,35). While in some cases active genes are hyperacetylated and contain H1 (10,31,37), it has also been reported that while H1 binds to acetylated oligonucleosomes, this binding inhibits transcription (53). In addition, studies have demonstrated that histone acetylation alters the capacity of histone H1 to condense chromatin (36) and that the presence of H1 affects the ability of transcription factors to interact with the DNA (19,39).…”
mentioning
confidence: 99%